2017
DOI: 10.1111/jmi.12566
|View full text |Cite
|
Sign up to set email alerts
|

Automatic diagnosis of vulvovaginal candidiasis from Pap smear images

Abstract: Vulvovaginal candidiasis (VVC) is the most common genital infections that are seen every day in clinics. This infection is due to excessive growth of Candida that are normally present in the vagina in small numbers. Diagnosis of VVC is routinely done by direct microscopy of Pap smear samples and searching for the Candida in the Pap smear glass slides. This manual method is subjective, time consuming, labour-intensive and tedious. This study presents a computer-aided diagnostic (CAD) method to improve human dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Owing to the crosssectional study design, the fact that Candida fungi have been found in cervical cancer samples and cervical cancer tissue has not been able to prove that the presence and invasion of Candida in exo/ectocervical tissue is a risk factor for cervical cancer. However, current results provide updated information regarding the coexistence of Candida invasion in exo/ectocervical tissue and the incidence of cervical cancer [27,[29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the crosssectional study design, the fact that Candida fungi have been found in cervical cancer samples and cervical cancer tissue has not been able to prove that the presence and invasion of Candida in exo/ectocervical tissue is a risk factor for cervical cancer. However, current results provide updated information regarding the coexistence of Candida invasion in exo/ectocervical tissue and the incidence of cervical cancer [27,[29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of blood, inflammatory cells, mucus and other debris makes the detection process unreliable. When the organisms are good in number in well-stained PAP smear, identification of candida species is not that difficult and a need for PAS also does not arise [7].…”
Section: Annals Of Clinical and Laboratory Research Issn 2386-5180mentioning
confidence: 99%